Identifikasi Pemanfaatan Permainan Tradisional Sasak bagi Pendidikan Anak Usia Dini di Masa Pandemi Covid-19 - Ni Made Sulastri (Universitas Pendidikan Mandalika, 2020)
This study aims to identify the types of traditional Sasak games that are suitable for early childhood and to find out the benefits of traditional Sasak games that are appropriate for early childhood development. The research method used was a survey. This research was conducted in the Ampenan District, Mataram City. This research data collection technique uses field notes, observations, and biographies. Analysis of the data in this study uses descriptive quantitative analysis. The results of this study indicate that there are identified types of games suitable for early childhood development during the Covid-19 pandemic. Traditional games are usually done with tools and without tools, sometimes also accompanied by singing. The benefits of traditional games are to develop aspects of child development, namely physical-motor, cognitive, language, creativity and social-emotional aspects.